Pengaruh Inklusi Keuangan dan Kredit Bermasalah Terhadap Kinerja Keuangan dengan Pengungkapan Pelaporan Berkelanjutan sebagai Pemoderasi - Leonardo Krishnanda; Nera Marinda Machdar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research was aimed to know the impact of financial inclusion and non performing loan on financial performance with sustainability reporting disclosure as moderator. Financial performance is measured by ROAA, ROAE, and net income. In this study, the sample used are the conventional bank listed in Indonesia Stock Exchange (BEI) in 2013-2018 with 34 sample by using a purposive sampling technique. This research used panel data regression method with random effect approach model. The results show that financial inclusion has no impact by ROAA and ROAE, but has positive impact on net income. Non performing loan has negative impact by ROAA, ROAE, and net income. Sustainability reporting disclosure does not strengthen nor weaken the impact financial inclusion and non performing loan on ROAA and ROAE. Sustainability reporting disclosure strengthen the effect of financial inclusion on net income. Sustainability reporting disclosure weaken the effect of non performing loan on net income.